Real Time Door Access Event Detection and Notification in a Reactive Smart Surveillance System - Abd Manap, Nurulfajar; Mat Ibrahim, Masrullizam (Springer Berlin Heidelberg, 2012)
The effectiveness of modern video surveillance systems critically depends on camera image quality and human operators’ reactivity. In this paper we present a door access event detection application in the context of a reactive smart surveillance system, which automatically notifies in real time the occurrence of events to registered users, through SMS alerts. The system utilizes two fixed IP cameras and a high resolution PTZ camera to acquire high quality images of the face of people entering the room. System users can access a web-based interface to review the event details, along with a short video clip and the high quality face images acquired. Experimental results demonstrate that the final system allows the PTZ camera to automatically acquire high-resolution images of faces and deliver them to system operators in real time.